KAJIAN AKTIVITAS ANTIOKSIDAN DAN ANTIMIKROBA EKSTRAK BIJI, KULIT BUAH , BATANG DAN DAUN TANAMAN JARAK PAGAR (Jatropha curcas L.) - Setyaningsih, Dwi; Nurmilah, Ovi Yulianti; Windarwati, Sri (UPN VETERAN JAWA TIMUR, 2010)
Jatropha curcas is one of potential bioenergy plant. Jatropha curcas also has great potential for the development of bio-products, medicines and consumer good since it contains some bioactive agents such as β-sitosterol, stigmasterol, curcin, flavonoid and 12-deoxyl-16-hydroxyphorbol (phorbol esther) that potentials as antioxidant and antimicrobial agent. The purpose of this research were to determine the yield of extract, antimicrobial and antioxidant activity from seed, fruit shell, stem and leaves of J. curcas. Seed, fruit shell, stem and blend of stem and leaves were extracted with three type of solvents. They were methanol, ethyl acetate and n-hexane. From the yield of extract, it could be concluded that seed of J.curcas L contained a lot of semi polar compounds (35,98%) and non polar compounds (32,27%), blend of stem and leaves contained a lot of polar compounds (9,75%) and J. curcas fruit shell contained a lot of polar compounds (5,96%). Antioxidant activity with scavenging effect on DPPH radical (1,1-diphenyl-2-picrylhidrazil) and antimicrobial activity using well diffusion method showed that methanol extract from J. curcas seed had the highest value of antioxidant and antimicrobial activity than other samples. The antioxidant activity of methanol extract from J. curcas seed was 93,40%, comparable with ascorbic acid as reference. The potency of antimicrobial activity of this extract could be seen from the bacterial inhibition zone diameter of 11.9 mm for E. coli and 14.83 mm for S. aureus.Keywords: Antimicrobial, antioxidant, Jatropha curcas L